2015 IEEE International Conference on Systems, Man, and Cybernetics 2015
DOI: 10.1109/smc.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Two Types of Fuzzy TOPSIS Method

Abstract: Abstract-Multi Criteria Decision Making methods have been developed to solve complex real-world decision problems. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is currently one of the most popular methods and has been shown to provide helpful outputs in various application areas. In recent years, a variety of extensions, including fuzzy extensions of TOPSIS have been proposed. One challenge that has arisen is that it is not straightforward to differentiate between the multiple va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Some of the advantages of TOPSIS methods are simplicity, rationality, comprehensibility, good computational efficiency and ability to measure the relative performance for each alternative in a simple mathematical form [25]. Madi et al [125] compared two types of TOPSIS and fuzzy TOPSIS techniques and found that the fuzzy TOPSIS technique is one of the most popular methods and is superior to crisp TOPSIS for multi-criteria ranking in decision-making. The merit of using a fuzzy approach is to assign the relative importance of attributes using fuzzy numbers instead of precise numbers, and this attribute has extended the TOPSIS to the fuzzy environment [126].…”
Section: Methodsmentioning
confidence: 99%
“…Some of the advantages of TOPSIS methods are simplicity, rationality, comprehensibility, good computational efficiency and ability to measure the relative performance for each alternative in a simple mathematical form [25]. Madi et al [125] compared two types of TOPSIS and fuzzy TOPSIS techniques and found that the fuzzy TOPSIS technique is one of the most popular methods and is superior to crisp TOPSIS for multi-criteria ranking in decision-making. The merit of using a fuzzy approach is to assign the relative importance of attributes using fuzzy numbers instead of precise numbers, and this attribute has extended the TOPSIS to the fuzzy environment [126].…”
Section: Methodsmentioning
confidence: 99%
“…This method has been successfully used in various areas, requiring multi-criteria decision making. The fuzzy version of the TOPSIS, introduced in (Chen, 2000) and elaborated in the follow-up research and publications (Chu, (2002); Mahdavi et al, 2008;Wang and Lee, 2009;Kaya and Kahraman (2011); Madi et al, 2015;Nădăban et al, 2016;Palczewski and Sałabun, 2019), laid down a methodological foundation for applications of the Z-number based versions of the TOPSIS (Yaakob and Gegov, 2015;Krohling et al, 2016;Wang and Mao, 2019).…”
Section: And Susilawatibmentioning
confidence: 99%
“…The fuzzy set theory uses membership functions to permit the gradual assessment of element membership in a set. Thus, a fuzzy set in may be represented as [17],…”
Section: ( ) { (23)mentioning
confidence: 99%
“…According to Madi et al [17] -A fuzzy number M is a convex normal fuzzy set M of the real line R such that [18]: There exists exactly one with ( ) ( is called mean value of M) and ( ) is piecewise continuous.‖ Among various fuzzy numbers like triangular fuzzy number (TFN), trapezoidal fuzzy number, bell-shaped fuzzy number, etc., TFN is the most commonly used due to its computational simplicity and intuitiveness. TFN is a triplet of three real numbers ( ) (see Fig.…”
Section: ( ) { (23)mentioning
confidence: 99%